Dermal tolerance and effect on skin hydration of an improved ethanol-based hand gel - Kampf, Günter; Muscatiello, Michael; Segger, Dörte (International Journal of Infection Control, 2009)
Alcohol-based hand gels have become a standard in hand hygiene in the United States but many of them are significantly less effective than liquid alcohol-based hand disinfectants. An improved ethanol-based gel (85%, w/w) with an efficacy equal to liquid products was investigated for dermal tolerance and skin hydrating properties which are essential to achieve a high compliance rate with hand hygiene. For the repetitive occlusive patch test 224 subjects were studied, 213 finished the study. Sterilium Comfort Gel was applied to one site on the back under an occlusive patch during an induction phase (9 applications over 3 weeks) and 2 weeks later to a virgin site on the back during a challenge phase (1 application). Sites were graded for skin reactions using a standardized scale 24 h after removal of the patches (induction phase and challenge phase) as well as 48 and 72 h later (challenge phase). To evaluate skin hydrating properties of the gel, treated skin of 23 subjects was compared to untreated skin. The gel was applied twice a day to the forearm for 14 days. Control corneometer values were taken before application of the gel and after 1 and 2 weeks. In the induction phase none of the 213 subjects had a skin reaction. In the challenge phase one subject had a barely perceptible skin reaction at one time point. Relative skin hydration on treated skin in comparison to the untreated control fields was significantly higher after one week by 7.7% (p = 0.0007; paired t-test for dependent samples) and after two weeks by 14.1% (p < 0.0001). The gel did not demonstrate a clinically relevant potential for dermal irritation or sensitization and significantly increased skin hydration after repetitive use and so could enhance compliance with hand hygiene among health care workers.